2010
DOI: 10.1007/s10943-010-9410-3
|View full text |Cite
|
Sign up to set email alerts
|

Health, Well-being, and Social Indicators Among Monks, Prisoners, and Other Adult Members of an Open University Cohort in Thailand

Abstract: This study has brought together two seemingly socially extreme population subgroups to compare their health and social well-being. These groups had in common restricted living arrangements and aspirational enrollment. As well, they are part of the population-based Thai Cohort Study (TCS) of 87,134 adult Open University students residing throughout the country. Analysis was restricted to men aged 20–39 years resulting in 711 monks, 195 prisoners and 29,713 other cohort members. For physical health, we have foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…One Thai study noted ‘suffering’ in Buddhism is similar to ‘psychological distress’ and another study reported that those who practised meditation had less distress (Tyson and Pongruengphant 2007; Wiist et al 2010). Our earlier baseline cohort data (2005) has shown high scores for ‘importance of religion when facing problems’ as well as belief in ‘importance of karma’ among cohort members (Yiengprugsawan et al 2010a).…”
Section: Discussionmentioning
confidence: 96%
“…One Thai study noted ‘suffering’ in Buddhism is similar to ‘psychological distress’ and another study reported that those who practised meditation had less distress (Tyson and Pongruengphant 2007; Wiist et al 2010). Our earlier baseline cohort data (2005) has shown high scores for ‘importance of religion when facing problems’ as well as belief in ‘importance of karma’ among cohort members (Yiengprugsawan et al 2010a).…”
Section: Discussionmentioning
confidence: 96%
“…A qualitative study in Thailand has supported the Buddhist view highlighting caregivers’ suffering, acceptance and compassion (Sethabouppha et al 2005). Thai cohort members overall have strongly affirmed the importance of karma and religion in their daily lives (Yiengprugsawan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although our study did not focus on finding a relationship between burden and demographic variables, our caregiver profile (a burdened wife of 67-68 years of age with a low educational level and no job) corresponds largely to the standard caregiver profile shown by other authors [ 4 , 32 , 43 , 44 ] that associates these variables with a greater degree of burden [ 45 , 46 , 47 , 48 ]. Some studies talk about the effect of culture [ 49 ] and religion [ 50 , 51 ] on caregivers, but we did not analyze these data, since 98.90% of our caregivers were Spanish and their religion, due to privacy reasons, was not requested.…”
Section: Discussionmentioning
confidence: 99%